IDEAS OF NATIONAL SOVEREIGNTY IN THE CONSTITUTION OF KAZAKHSTAN AND THEIR IMPLEMENTATION - Khuandag Bazhay; Akhmet Bergengul (International Journal of Innovative Technologies in Social Science, 2021)
The article reveals Kazakhstan’s model of implementation of the ideas of national sovereignty in the context of interethnic harmony, internal national unity and modernization of society in the Constitution. Comparative legal analysis of scientific conclusions related to the principles of the idea of popular sovereignty is carried out. The importance of strengthening state power and social harmony in the creation of a state governed by the rule of law is emphasized, logical conclusions and thoughts are summed up.